Optimasi Isolasi DNA Cabai (Capsicum annuum L.) Berdasar Perbedaan Kualitas dan Kuantitas Daun serta Teknik Penggerusan - Ferniah, Rejeki Siti; Pujiyanto, Sri (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2013)
Complete genome of chili has not been reported.The first step to study the genome is DNA isolation, so it is necessary to optimize the protocol to get an optimum DNA. This research aimed to optimize chili DNA isolation by variate the quantity and quality of chili leaves as row material and variate the grinding technique. DNA isolation was done using commercial kit without liquid nitrogen, and analyzed by agarose gel electrophoresis. The results showed that frozen chili leaf yields more DNA than fresh leaf, 0,1 g of leaf got optimum DNA, and grinding in mortar was better than in microtube. Â Key words: DNA,Â isolation, Capsicum annuum